THE INFLUENCE OF USING ANIMATED FIMS IN SPEAKING ABILITY IMPROVEMENT - Riri Narasati Narasati (JALL (Journal of Applied Linguistics and Literacy), 2021)
The background of this research is the lack of students’ interest in learning Speaking which can be seen from the assessed scoring. The researcher made a teaching media, which is the animated film that is used in learning Speaking. It is hoped that by using the animated film media, students will be more interested and more active in improving their Speaking skills. In conducting this research, the Descriptive Statistic method using the class control and the class experiment is used. The data obtained are Pre Test and Post Test data which are then processed using Wilcoxon. This way, at the end of the research it can be concluded that the use of animated films can improve the Speaking skills because there is significant score difference between before and after using animated films as for Speaking learning media. (not more than 250 words).            Keywords: Influence, Speaking, Animated Film,